SOCIO-ECONOMIC STRENGTHENING STRATEGY OF LPD TUKAD MUNGGA TRADITIONAL VILLAGE, BALI PROVINCE - Dyah Poespita Ernawati; Yass Andria (Jurnal Ekonomi, 2022)
LPD Tukad Mungga can be considered in improving and supporting the surrounding community's economy through an entire work program that is understood by all villages and indigenous villages on the island of Bali. The main goal of the Tukad Mungga Traditional Village LPD is to strengthen the economy of indigenous villages, increase the independence and welfare of indigenous villages, and maintain the resilience and sustainability of Balinese culture based on the Tri Hita Karana philosophy (Parahyangan, Pawongan, and Palemahan). Analysis SOAR, loan asset ratio (LAR), loan deposit ratio (LDR), and return on equity (ROE) show that the lpd of tukad mungga indigenous village that thrives has been proven to improve the economic development of indigenous villages, increase capital and large LPD assets. Effective special strategies in the socioeconomic strengthening of indigenous villages in Bali Province have become a buffer for the growth and development of Balinese culture, providing donations and social assistance for the development of indigenous villages. Meanwhile, leadership, optimism and consistency of managers, customertrust, and IT-based services have increased the financial effectiveness of lpd tukad Mungga traditional village. This means that for back up finance, LPD is superior and chosen by customers, especially small and micro-entrepreneurs in their business when compared to formal financial institutions, so that the entrepreneurial spirit and living standards of the community can be encouraged and improved through funding from the LPD of tukad Mungga traditional village.